3(x-4)-2(3x-1)=17
3x-12-6x+2=17
3x-6x=17+12-2
-3x=27
x=27/-3= -9
2007-09-18 05:37:10
·
answer #1
·
answered by alpha 7
·
0⤊
0⤋
No, it's not 3. It's (-9)...
3x -12 -6x+2=17
-3x= 17 +12 -2
-3x= 27
x= 27/-3
x=-9
2007-09-18 05:41:53
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
1) 3X - 12 - 6X + 2 = 17
2) -27 = 3X
3) X = -9
Can you follow what I did from step 1 to step 2?
1) I added 6X to the other side of the equation and then subtracted 3X giving me 3X on the right side. Then I combined -12 and + 2 on the left side which equals -10. Then I subtracted 17 from -10 giving me -27.
2007-09-18 05:34:12
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
3(x - 4) - 2(3x - 1) = 17
3x - 12 - 6x + 2 = 17
- 3x = 27
x = - 9
2007-09-18 05:36:29
·
answer #4
·
answered by Jun Agruda 7
·
3⤊
0⤋
3x - 12 - 6x + 2 = 17
-3x - 10 = 17
-3x = 27
3x = - 27
x = - 9
2007-09-18 11:14:26
·
answer #5
·
answered by Como 7
·
2⤊
0⤋
3 (x-4) - 2(3x-1)=17
3x -12 -6x +2 -17=0
-3x -27 = 0
3x = 27
x=9
2007-09-18 06:08:09
·
answer #6
·
answered by Kid 3
·
0⤊
0⤋
3x-12-6x+2=17=>3x=-27=>x=-9
2007-09-18 05:34:59
·
answer #7
·
answered by lord 2
·
0⤊
0⤋
3(x-4)-2(3x-1)=17
3x-12-6x+2=17
-3x-10=27
-3x=27
x=-9
2007-09-18 05:42:26
·
answer #8
·
answered by Will 4
·
0⤊
0⤋
3x-12-6x+2=17
-3x-10=17
-3x=27
-x=9
x=-9
2007-09-18 05:34:30
·
answer #9
·
answered by Darkwolf 5
·
0⤊
0⤋
work out the parenthesis:
--> 3(x-4)= 3x-12
--> -2(3x-1)= -6x+2
combine like terms:
--> 3x-6x= -3x
--> -12+2= -10
add +10 to both sides:
--> -10+10 cancel out
--> 17+10=27
divide -3 to both sides, leavin 'x' by itself:
--> -3/-3 cancel out
--> 27/-3= -9
x= -9 (is the answer)
2007-09-18 05:46:58
·
answer #10
·
answered by **annie anytime** 3
·
0⤊
1⤋